Initial Experience and Usage Patterns With the Owlet Smart Sock Monitor in 47, 495 Newborns. (28th November 2017) - Dangerfield, Michelle I.; Ward, Kenneth; Davidson, Luke; Adamian, Milena
We report the largest experience, to our knowledge, of home cardiorespiratory monitoring in 47, 495 newborns using the novel Owlet Smart Sock (OSS) technology (October 2015 to May 2017). On average, 47, 495 newborns were monitored for 6 months, 4.5 d/wk, 9.9 h/d. Continuous readings of oxygen saturation and heart rate were obtained from 39, 626 full-term newborns. OSS users were likely first-time parents in their 30s with at least a college degree; 37% had a healthcare professional in the family; and 28% were at or below median income level per the US Census Bureau. "Peace of mind" was the reason to own an OSS in 75%, and 82% of parents followed Safe Sleep Guidelines. A total of 94% of parents reported a better quality of sleep. The fast and continuous pace of device adoption and reported experience suggest excellent parental acceptance of the OSS. Prospective studies are warranted to further evaluate its applications in the high-risk newborn population.